Synaptic input to brain tumors: clinical implications - Venkataramani, Varun; Tanev, Dimitar Ivanov; Kuner, Thomas; Wick, Wolfgang; Winkler, Frank (Neuro-Oncology, 2021)
The recent discovery of synaptic connections between neurons and brain tumor cells fundamentally challenges our understanding of gliomas and brain metastases and shows how these tumors can integrate into complex neuronal circuits. Here, we provide an overview of glutamatergic neuron-to-brain tumor synaptic communication (NBTSC) and explore novel therapeutic avenues. First, we summarize current concepts of direct synaptic interactions between presynaptic neurons and postsynaptic glioma cells, and indirect perisynaptic input to metastatic breast cancer cells. We explain how these novel structures drive brain tumor growth and invasion. Second, a vicious cycle of enhanced neuronal activity, including tumor-related epilepsy, and glioma progression is described. Finally, we discuss which future avenues to target NBTSC appear most promising. All in all, further characterization of NBTSC and the exploration of NBTSC-inhibiting therapies have the potential to reveal critical vulnerabilities of yet incurable brain tumors.
Advance access date 5 July 2020
Gesehen am 18.06.2021